ANALISIS YURIDIS TERHADAP PASAL 27 AYAT 3 UNDANG-UNDANG NOMER 19 TAHUN 2016 TENTANG INFORMASI DAN TRANSAKSI ELEKTRONIK DIKAITKAN DENGAN HAK ASASI MANUSIA - Sinaga, Lusya Ermauli Br; Effendi, Erdianto; Artina, Dessy (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
Freedom of expression is a fundamental part of human rights. In addition to international recognition through the Universal Declaration of Human Rights (DUHAM) of 1948 or Universal Declaration of Human Rights, also nationally Indonesia is very insistent mention of freedom of expression in the Constitution of 1945. In Article 28E Paragraph (3) of the 1945 Constitution which states,